2022
DOI: 10.3390/foods11152327
|View full text |Cite
|
Sign up to set email alerts
|

Extraction, Structural Analysis, and Biofunctional Properties of Exopolysaccharide from Lactiplantibacillus pentosus B8 Isolated from Sichuan Pickle

Abstract: Two novel exopolysaccharides, named LPB8-0 and LPB8-1, were isolated and purified from Lactiplantibacillus pentosus B8. Moreover, their structure and bioactivities were evaluated through chemical and spectral means. The study results demonstrated that LPB8-0 was primarily composed of mannose and glucose and had an average molecular weight of 1.12 × 104 Da, while LPB8-1 was composed of mannose, glucose, and galactose and had an average molecular weight of 1.78 × 105 Da. Their carbohydrate contents were 96.2% ± … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…There is plenty of well-described evidence of the antioxidant activity of EPSs synthesised by Lactobacillus species, such as the EPSs produced by L. helveticus MB2–1, L. acidophilus P185, L. plantarum S123, L. plantarum RO30, L. plantarum MC5, L. casei NA-2, and L. pentosus . 23–29 Data obtained in this work showed the great antioxidant activity of many of the EPS crude extracts obtained from Lactiplantibacillus strains, especially LPG1.…”
Section: Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…There is plenty of well-described evidence of the antioxidant activity of EPSs synthesised by Lactobacillus species, such as the EPSs produced by L. helveticus MB2–1, L. acidophilus P185, L. plantarum S123, L. plantarum RO30, L. plantarum MC5, L. casei NA-2, and L. pentosus . 23–29 Data obtained in this work showed the great antioxidant activity of many of the EPS crude extracts obtained from Lactiplantibacillus strains, especially LPG1.…”
Section: Resultsmentioning
confidence: 71%
“…33 L. pentosus B8 exhibited an EPS production yield of 1401 mg L −1 in an MRS culture medium supplemented with 40 g L −1 sucrose at 30 °C. 29 Additionally, L. pentosus KS-27, isolated from sucuk, produced 991 mg L −1 of EPS in an MRS medium supplemented with 100 g L −1 sucrose. 34 Finally, L. pentosus LZ-R17 produced 185.20 mg L −1 of crude EPS when cultured in a pasteurised milk medium.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, an overnight culture of bacteria (1 × 10 8 CFU/mL) was independently inoculated into MRS broth containing sugars as described above and incubated at 37 °C for 48 h. The bacterial culture was then removed from the extract by centrifugation (10,000× g , 20 min, 4 °C). EPSs were separated from the cell-free supernatant by the addition of ice-cold absolute ethanol (two volumes) and incubation for 2 days with refrigeration [ 79 ]. The precipitated EPSs from liquid culture (EPSQ) were centrifuged and dissolved in double distilled water and dialyzed using a Midi dialysis kit (cat # PURD10005-1KT, Sigma-Aldrich, St. Louis, MO, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Some commonly used methods for the purification of exopolysaccharides include Sevag, TCA, ion exchange chromatography, and diethylaminoethyl (DEAE)-cellulose column chromatography methods [105][106][107][108] . Additional methods, such as gel filtration and size exclusion chromatography, can also be used during the purification process [109,110] . For example, Pei et al [110] reported the application of gel filtration to purify levan produced by Bacillus megaterium PFY-147 through a Sephadex column, and EPS was eluted with Milli-Q water at a flow rate of 0.2 mL/min.…”
Section: Extraction Methodsmentioning
confidence: 99%
“…The different methods used for EPS characterization are shown in Table 1. To determine the average molecular weight (MW), high-performance size-exclusion chromatography (HPSEC) with refractive index (RI) and multi-angle laser light scattering (MALLS) were used [109] . Gel permeation chromatography (GPC) using RI and MALLS as detectors was also used to determine the MW of EPS [127] .…”
Section: Extraction Methodsmentioning
confidence: 99%